Enhanced Solubility and Permeability of Naringenin Across Non-Everted Sacs of Rat Small Intestine by Lipid Nanocapsules - Vakilzadeh, Hamed; Varshosaz, Jaleh; Soghrati, Sahel (Recent Patents on Nanotechnology, 2021)
Background: Naringenin (NRG) has many health benefits, including; anti-atherogenic, antiinflammatory, antitumor, and anticancer activity, as well as improvement of lipid metabolism. However, its use is limited due to its low solubility and bioavailability. Objectives: The aim of the present patent study was the preparation and optimization of NRG loaded Novel Lipid Nanocapsules (LNCs) for the improvement of NRG solubility and gut permeability. Methods: Studied variables included; Solutol® HS15 and NRG concentration and the ratio of cold diluent water to primary emulsion. The storage stability of the LNCs was evaluated for 32 days and thermal analyses were conducted by Differential Scanning Calorimetry (DSC). The antioxidant properties of the NRG in LNCs were studied by measuring the 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity. The enhancement of permeation of NRG by the LNCs from the intestine was evaluated by the non-everted gut sac method. Results: The optimized NRG-LNCs had a hydrodynamic diameter of 29.41±1.25 nm, a low polydispersity index, and high entrapment efficiency of 99.25±2.31%. The LNCs could retain NRG radical scavenging activity, showed good storage stability, and significantly improved NRG solubility (69 fold) and permeation through non-everted rat intestinal sac (4.33 fold). Conclusion: LNCs of NGR enhance solubility and intestinal permeability of this flavonoid and may be useful in the improvement of its bioavailability.
Keywords: gut permeation